Direct Glutamatergic Signaling From Midbrain Dopaminergic Neurons Onto Pyramidal Prefrontal Cortex Neurons - Pérez-López, José Luis; Contreras-López, Rubén; Ramírez-Jarquín, Josué O.; Tecuapetla, Fatuel (Frontiers in Neural Circuits, 2018)
The dopaminergic neurons of the ventral tegmental area (VTA) have been identified with the ability to co-release dopamine and glutamate. This ability was first documented in the nucleus accumbens but showed to be absent in the dorsal striatum. Recently the ability to release glutamate from a subpopulation of the VTA dopaminergic neurons has been shown to control the prefrontal cortex excitation through the exclusive innervation of GABAergic fast spiking interneurons. Here, using an optogenetic approach, we expand this view by presenting that the VTA dopaminergic neurons do not only innervate interneurons but also pyramidal prefrontal cortex neurons. This finding opens the range of possibilities for the VTA dopaminergic neurons to modulate the activity of prefrontal cortex.